ENGINEERING OF LOW-TEMPERATURE MAGNETIC FIELD SENSORS BASED ON HETEROSTRUCTURES SI/SIO2/NI - E. Yu. Kaniukov; S. E. Demyanov (Приборы и методы измерений, 2015)
Results of investigations of electrical and magnetoresistive characteristics of Si/SiO2/Ni heterostructures obtained using the swift heavy ion track technology are presented. The presence of a positive magnetoresistance growing up with decreasing temperature and reaching 600 % at T ~ 25 K is determined. This result makes it possible to create highly-sensitive magnetic field sensor devices for space applications, which operates at a liquid hydrogen cooling. The prospects of the creation of magnetic-field sensors using alternating layers of ferromagnetic and nonmagnetic metals in the nanopores are determined. The possibility of application of the «Tunable Electronic Material in Pores in Oxide on Semiconductors» concept on this concern is demonstrated.